Investigations of the Influence of Ignition on the Dynamic Vivacity of Propellants - Radosław TRĘBIŃSKI (Badania wpływu zapłonu na krzywe dynamicznej żywości prochów, 2019)
The paper presents an attempt to determine the dynamic vivacity functions of propellants with taking into account a parallel burning of the black powder igniter and the tested propellant. The approach is based on presented results of closed vessel tests, proving that the burning of the tested propellant starts before complete burning of the black powder igniter. Basing on closed vessel tests results for black powder, its dynamic vivacity function was determined. It was used for a prediction of the partial pressure of black powder combustion products in the case when black powder was used as an igniter. Dynamic vivacity curves are compared with the dynamic vivacity curves calculated at the assumption that the combustion of the main charge starts after the complete burning of the igniter. Obtained results show that the considered approach fails due to a very complex interaction between the igniter and the tested propellant.
Keywords: Badania pirostatyczne materiałow miotających